A Conceptual Model for the Impact of Climate Change on Fox Rabies in Alaska, 1980–2010. (4th March 2013) - Kim, B. I.; Blanton, J. D.; Gilbert, A.; Castrodale, L.; Hueffer, K.; Slate, D.; Rupprecht, C. E.
Summary The direct and interactive effects of climate change on host species and infectious disease dynamics are likely to initially manifest\ at latitudinal extremes. As such, Alaska represents a region in the United States for introspection on climate change and disease. Rabies is enzootic among arctic foxes (Vulpes lagopus) throughout the northern polar region. In Alaska, arctic and red foxes (Vulpes vulpes) are reservoirs for rabies, with most domestic animal and wildlife cases reported from northern and western coastal Alaska. Based on passive surveillance, a pronounced seasonal trend in rabid foxes occurs in Alaska, with a peak in winter and spring. This study describes climatic factors that may be associated with reported cyclic rabies occurrence. Based upon probabilistic modelling, a stronger seasonal effect in reported fox rabies cases appears at higher latitudes in Alaska, and rabies in arctic foxes appear disproportionately affected by climatic factors in comparison with red foxes. As temperatures continue a warming trend, a decrease in reported rabid arctic foxes may be expected. The overall epidemiology of rabies in Alaska is likely to shift to increased viral transmission among red foxes as the primary reservoir in the region. Information on fox and lemming demographics, in addition to enhanced rabies surveillance among foxes at finer geographic scales, will be critical to develop more comprehensive models for rabies virus transmission in the region.